Beyond the Economic Gaze: Childbearing during and after recessions in the Nordic countries - Chiara Comolli; Gerda Neyer; Gunnar Andersson; Lars Dommermuth; Peter Fallesen; Marika Jalovaara; Ari Klaengur Jonsson; Martin Kolk; Trude Lappegard (Turun yliopisto ja THL, 2022)
Abstract: During the 2010s, fertility rates fell across the Nordic region. The onset of these
declines seems linked to the Great Recession of 2008–2009 but their continuation cannot easily
be linked to subsequent economic change. The 1990s, too, brought episodes of economic crises
to the Nordic region that were followed by different degrees of fertility decline. In this study,
we provide an empirical overview of parity-, age- and education-specific fertility developments
in the five Nordic countries in the wake of the economic recessions in 2008 and the early 1990s,
respectively. We demonstrate a high degree of heterogeneity in fertility developments across
countries after 1990, whereas after 2008, the trends are much more similar across the five
countries. Likewise, the educational differences in birth hazards that characterized the
developments after 1990 were much smaller in the initial years after 2008–2009. This reversal
from heterogeneity to homogeneity in the fertility response to recessions calls for an expansion
of theories on the cyclicality of fertility in relation to uncertainty and economic and social
change. In our discussion, we consider the role of a set of factors that also incorporates the state,
crisis management, and perceptions of economic and welfare uncertainty.